The myrour of recluses: a Middle English translation of Speculum inclusorum - Harley, Marta Powell (Fairleigh Dickinson Univ. Press [u.a.], 1995)
The Myrour of Recluses provides an edited text of British Library MS. Harley 2372, the only manuscript preserving the Middle English translation of the fourteenth-century Speculum Inclusorum. Of the four-part Latin original, the Middle English translation preserves the preface and all four chapters of Part 1 (discussing the motives for embracing closure) and the first two chapters of Parts 2 and 3 (deleting from each part only the third chapter on reading). Thus, the Middle English Myrour of Recluses treats fully the four motives for choosing enclosure and amply examines the nature and practice of prayer and meditation. The Myrour of Recluses draws throughout on devotional and doctrinal material familiar to the general audiences of the popular religious manuals. Scriptural quotations are plentiful. The ascetic advice and the devotional and doctrinal instruction in The Myrour of Recluses serve the author's higher aim of securing for the recluses "the sweetness of the love of God and of contemplation." The edition presents the entire surviving Middle English text. Where chapters of the Middle English Myrour of Recluses are fragmentary, bracketed Modern English translations of the Latin original are supplied (with the Latin passages printed in Appendix A). In addition to a physical description of the manuscript, the introduction to the edition offers an assessment of the translator's aims and a consideration of the work's place within the vast body of Middle English religious prose. Following the edited text, the textual and explanatory notes address unusual emendations and unfamiliar words or allusions. Indices of the names and scriptural quotations found in the text are provided in Appendices B and C.